RESPON DUA VARIETAS TANAMAN SELADA (Lactuca sativa L.) TERHADAP MACAM NUTRISI PADA SISTEM HIDROPONIK - Catur Wasonowati; Sinar Suryawati; Ade Rahmawati (Agrovigor, 2013)
Lettuce (Lactuca sativa L) is a common vegetables crops grown in the highland and lowlands.  A sample hydroponic lettuce cultivation provides an sources an alternative for farmers who have a narrow area, so that can server as an adequate source of income.  Providing nutrients to the two varienties of lettuce are expected to yield maximum production.  This tudy aims to determine the effect of nutrients on two varieties of lettuce plants.            The study was conducted in the greenhouse Agroekoteknologi Departement Faculty of Agriculture, University Trunojoyo Madurese from January to March 2011.  The method used was a factorial experiment based on Completely Randomized Design (CRD) with three replicates consisting of two treatment factors, the first factor are two different varieties of lecctuce and the second factor are two differwnt kinds of nutrients.            The results showed that the chief varieties of butter (V1) produces the number of leaves and dry biomass is higher than the varieties of cos (V2).  Nutrition in V1 generate the number of leaves, wet biomass, dry biomass, and root length was higher than without the provision of (N0). V1 responses to nutrient hidrogroup (N1) resulted in higher leaf number than nutrition greentonik (N2), but the provision of dry biomass yield N2 higher than N1. Nutrition on V2 generate the number of leaves, wet biomass and dry biomass was higher than N0. V2 response to the provision of N1 and N2 produce the number of leaves, wet biomass, dry biomass, and root length are not significantly different.Key word : lettuce, varieties, nutrition, simple hydroponics